The Relationship Between Coping Mechanism and Adherence to Hemodialysis Therapy on Chronic Renal Disease in Hemodialysis Room - Trisha Fitriani; Dwi Nur Aini; Nana Rohana (Proceedings of the International Conference on Nursing and Health Sciences, 2021)
Chronic renal failure is a disease caused by a prolonged decline in kidney function. One of the treatments performed by patients with chronic kidney failure is hemodialysis therapy. Hemodialysis therapy is carried out continuously and may result in patient psychosocial pressure. Coping mechanisms are adaptive and maladaptive. Adaptive coping mechanisms are needed by patients with chronic renal failure to improve compilance to hemodialysis therapy. The purpose of this study was to determine the relationship between coping mechanisms and compilance to hemodialysis therapy in chronic renal failure in the Hemodialysis Room of RSUD RA. Kartini Jepara. This research was quantitative research using cross sectional apporach. This research was conducted on 42 samples using purposive sampling technique. Processing data using the Spearman Rank correlation test. Results this research, respondents who had adaptive coping mechanisms were 41 people (97.6%), 1 person (2.4%) had maladaptive coping mechanisms. Respondents who were obedient in undergoing hemodialysis were 38 people (90.5%) and 4 people who were not compliant (9.5%). The statistics test results p value = 0,001 and Tcount = 0,481. Conclusion, Ha was accepted and H0 was rejected that means that there was a relationship between coping mechanisms and compliance with hemodialysis therapy in patients with chronic renal failure in the Hemodialysis Room of RSUD RA. Kartini Jepara.